2021
DOI: 10.1016/j.jtho.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Overall Survival From KEYNOTE-021 Cohort G: Pemetrexed and Carboplatin With or Without Pembrolizumab as First-Line Therapy for Advanced Nonsquamous NSCLC

Abstract: Introduction: In cohort G of KEYNOTE-021 (NCT02039674), first-line pembrolizumab plus pemetrexed-carboplatin significantly improved the objective response rate and progression-free survival versus chemotherapy alone with manageable toxicity in advanced nonsquamous NSCLC. We report the long-term outcomes from this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 6 publications
2
116
1
1
Order By: Relevance
“…The magnitude of treatment effect favoring pembrolizumab plus pemetrexedeplatinum was consistent with that reported in an analysis from cohort G of the phase II KEYNOTE-021 study with w4 years of follow-up, which reported a median OS of 34.5 months with pembrolizumab plus pemetrexedecarboplatin versus 21.1 months with pemetrexedecarboplatin (HR, 0.71). 9 Notably, median OS was longer in both arms of KEYNOTE-021 cohort G than in the corresponding treatment arms in KEYNOTE-189. This difference in outcomes may be explained, in part, by the inclusion of patients in KEYNOTE-021 with better prognosis (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…The magnitude of treatment effect favoring pembrolizumab plus pemetrexedeplatinum was consistent with that reported in an analysis from cohort G of the phase II KEYNOTE-021 study with w4 years of follow-up, which reported a median OS of 34.5 months with pembrolizumab plus pemetrexedecarboplatin versus 21.1 months with pemetrexedecarboplatin (HR, 0.71). 9 Notably, median OS was longer in both arms of KEYNOTE-021 cohort G than in the corresponding treatment arms in KEYNOTE-189. This difference in outcomes may be explained, in part, by the inclusion of patients in KEYNOTE-021 with better prognosis (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…In non-small lung cancer (NSCLC), the current treatment for KRAS mutant patients relies on chemotherapy, with an average overall survival (OS) of 22 months, which is less than desired. 1 Since previous efforts failed to specifically target KRAS, researchers began to indirectly target KRAS through its role in various signaling pathways. Unfortunately, targeting KRAS dependencies in NSCLC has highlighted the difficulty in the effective inhibition of indirect targeting of KRAS.…”
Section: Introductionmentioning
confidence: 99%
“…In <5 years, the availability of novel therapeutics has transformed the landscape of KRAS treatments, and a target that was once considered “undruggable” now has several therapeutic inhibitors undergoing clinical trials. 10 , 11 , 12 There are essentially four novel approaches to target KRAS that can be divided into targeted therapies and immunotherapies, potentially in combination with one another: 1 a novel class of direct KRAS inhibitors that specifically inhibit the G12C mutations through direct interaction with the cysteine residue, as well as a somewhat broader approach using a pan-KRAS inhibitor that does not attempt to inhibit specific mutations; 2 novel signaling inhibitors that can inhibit chronic activation of KRAS-dependent pathways; 3 immune checkpoint inhibitors (ICIs) that can be used in combination with other approaches; 4 and approaches that take advantage of the neoantigen feature of mutated KRAS protein and attempt to improve the T cell response. Therefore, we present in this review recent advances in therapeutic options from a clinical standpoint, to understand the mechanisms of these inhibitors and potential future considerations regarding KRAS and therapeutic efficacy in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…While the initial analysis after a median follow‐up of 10.6 months showed no difference in OS (HR: 0.90; 95% CI: 0.42–1.91), outcomes improved with time. An update after a median follow‐up of 49.4 months showed that the addition of pembrolizumab to carboplatin plus pemetrexed improved RR (58% vs. 33%), PFS (median: 24.5 vs. 9.9 months; HR: 0.54) and OS (median: 34.5 vs. 21.1 months; HR: 0.71), despite a 70% crossover rate 35 . Based on the initial report, pembrolizumab with carboplatin plus pemetrexed received accelerated FDA approval on May 10, 2017.…”
Section: Metastatic Nsclcmentioning
confidence: 99%